Prediksi Financial Distress Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Randy Kurnia Permana; Nurmala Ahmar; Syahril Djadang (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Financial Distress Prediction in Manufacturing Companies at Indonesian Stock ExchangeThis study aims to identify, analyze, demonstrate and test the differences in health status between the model results Grover, Springate, and Zmijewski. The model used by investors who will invest in the company. This study has a characteristic that is tested three models and find the one best model. Data was tested using chi-square test. Results showed Hypothesis 1 accepted that there are differences in health status in the test model of Grover, Springate, and Zmijewski on manufacturing companies listed on the Stock Exchange 2006-2015. Model Springate is the best predictive model than the model Grover and Springate, because it has more components than the other models and models Springate have EBIT  To Current Liabilities component is how much profit the ability to pay debts. This component is a very important component to see financial distress, due to financial distress occur because one debt that not covered by the companyDOI: 10.15408/ess.v7i2.4797